Postcoloniality, proverbs and intercultural dialogue: translating African postcolonial texts, things fall apart and arrow of god, into German (2013)
The proverb is not only an oral form that enhances immediate communication and mends social conflict, especially in traditional societies, it is also a vista to the knowledge and understanding of the cultural other at the various levels of content and context of the proverb. This latter function makes the use of proverbs in African postcolonial literary texts particularly meaningful and significant in the relations of asymmetry that characterises ex-coloniser and ex- colonised societies in textual cultural relations mediated through translation. The cultural knowledge and cultural identity markers borne in proverbs can, however, be contested, distorted or affirmed in translations: thus making proverb translation a unique space of cultural identity and meaning contest. Illustrating with proverbs purposively selected from Chinua Achebe’s Things Fall Apart and Arrow of God and their German translations, this article demonstrates the ‘embeddedness’ of proverbs in the conflictual dialogue and discourse of postcolonial textual relations and identity ascription. It emphasises the need that the approaches and strategies for their translation take cognisance of this dialogic discourse and of the authorial communicative purpose of the texts.